Churches, City and National Identity in Mid-19th Century Edinburgh - Clarisse Godard Desmarest (Angles, 2020)
This paper reflects on the importance of Edinburgh’s Lawnmarket and Castlehill area in the context of the 1843 Disruption which saw the separation of the Free Church from the Established Church of Scotland mainly over the issue of the Church’s relationship with the State. Edinburgh’s Holy Corner, as it is colloquially known, refers to the Bruntsfield and Morningside junction with four churches; but this paper argues that by the mid-19th century the Lawnmarket area was an even ‘holier’ corner. Within a discrete area west of St Giles — Edinburgh’s Cathedral — and almost touching one another were built the Church of Scotland’s headquarters at Victoria Hall (or Old Tolbooth Church; today, ‘The Hub’), and for the Free Church, its headquarters at New College. These two buildings alone (other churches were constructed in closest proximity) show that for both organisations, Edinburgh in its old role as the national capital was deemed vital. This national importance was here emphasised (or resurrected) and intentionally exploited by each organisation for the purpose of demonstrating its own historical legitimacy and validity, each regarding itself as the national Church continuing. That it was not simply Edinburgh, but the Old Town, which was chosen, emphasised yet further the heritage, continuity and historic validity claimed by the two ‘ancient’ Churches; the Tron Church was a lesser ornament, as the fire of 1824 had diminished its prestige of antiquity. A major — if perhaps inadvertent — consequence was that the Old Town’s renewal was now securely in hand thanks to these competing churches; and all following the effective reincarnation in dressed ashlar of St Giles in the 1830s by William Burn. Both organisations being based in Edinburgh made the city not simply the two Churches’ national headquarters, but also, given the impact of missionary work and Empire, the international hub to which every congregation looked to for leadership and support. By focusing on a small area at the very heart of the Old Town of Edinburgh, this paper brings together a key moment of ecclesiastical history, whose significance goes well beyond Edinburgh itself, with important developments in urban design and architectural history.